Hyperbaric Oxygen Therapy in Managing Minimally Invasive Aesthetic Procedure Complications: A Report of Three Cases - Oley MH; Oley MC; Mawu FO; Aling DMR; Faruk M (Dove Medical Press, 2022)
Mendy Hatibie Oley,1- 3 Maximillian Christian Oley,3- 5 Ferra Olivia Mawu,6 Deanette Michelle R Aling,3 Muhammad Faruk7 1Plastic Reconstructive and Aesthetic Surgery Division, Department of Surgery, Faculty of Medicine, Sam Ratulangi University, Manado, Indonesia; 2Plastic Reconstructive and Aesthetic Surgery Division, Department of Surgery, R. D. Kandou Hospital, Manado, Indonesia; 3Hyperbaric Centre, Siloam Hospital, Manado, Indonesia; 4Division of Neurosurgery, Department of Surgery, Faculty of Medicine, Sam Ratulangi University, Manado, Indonesia; 5Division of Neurosurgery, Department of Surgery, R. D. Kandou Hospital, Manado, Indonesia; 6Department of Dermatology and Venereology, Faculty of Medicine, Sam Ratulangi University, Manado, Indonesia; 7Department of Surgery, Faculty of Medicine, Hasanuddin University, Makassar, IndonesiaCorrespondence: Mendy Hatibie OleyPlastic Reconstructive and Aesthetic Surgery Division, Department of Surgery, Faculty of Medicine, Sam Ratulangi University, Jalan Raya Tanawangko No. 56, Malalayang Satu Barat, Malalayang, Manado, 95162, IndonesiaFax +62431-863786Email mendy.hatibie@unsrat.ac.idIntroduction: Minimally invasive aesthetic procedures such as filler injections and thread lifts have gained popularity recently. Complications from these aesthetic procedures are difficult to avoid. This increasing public health concern requires a combination of effective therapeutic modalities. Hyperbaric oxygen therapy (HBOT) has generated favorable results in treating a diversity of wounds, inflammation, and infection.Case Presentations: Three cases with complications arising from aesthetic procedures were described in this report. The patients were all female, with ages ranging from the late-twenties to mid-fifties. Two patients experienced complications from filler injections, one of which progressed to a parotid gland infection due to a placental extract filler while the other was caused by a hyaluronic acid filler. The third patient had notable excoriations and inflammation on both cheeks following a thread lift procedure. Alongside antibiotics and other symptomatic therapies, the patients received multiple, 90-minute HBOT sessions at 2.4 ATA over the course of one to two weeks. The wounds were frequently monitored to evaluate the healing progress.Discussion: Complications from facial rejuvenation procedures can be disastrous. They expose the patient to the risk of developing vascular occlusions and skin infections that require prompt and effective treatment. Multiple treatment options (eg, frequently massaging the affected area, warm compresses, aspirin, and antibiotics) have been used to treat these complications. HBOT serves a valuable purpose in restoring adequate tissue perfusion in cases of filler-induced vascular occlusion and infection. Moreover, HBOT assists in restoring tissue injury and reducing inflammation following thread lift procedures.Conclusion: HBOT has proven helpful as a treatment adjunct toward counteracting the effects of minimally invasive aesthetic procedures in several cosmetic-related cases.Keywords: hyperbaric oxygen therapy, filler injection, thread lift, complications, aesthetic procedures